13th AIAA/CEAS Aeroacoustics Conference (28th AIAA Aeroacoustics Conference) 2007
DOI: 10.2514/6.2007-3532
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Liner Characteristics in the NASA Langley Curved Duct Test Rig

Abstract: The Curved Duct Test Rig (CDTR), which is designed to investigate propagation of sound in a duct with flow, has been developed at NASA Langley Research Center. The duct incorporates an adaptive control system to generate a tone in the duct at a specific frequency with a target Sound Pressure Level and a target mode shape. The size of the duct, the ability to isolate higher order modes, and the ability to modify the duct configuration make this rig unique among experimental duct acoustics facilities. An experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…Figure 1 is a photograph of the Curved Duct Test Rig. A brief description of the test rig is presented here, and more details are found in previous papers by the authors [2,3]. Air is supplied to the test rig from a centralized air supply and passes through a set of mufflers (not shown in the photograph), an elbow with turning vanes, and a flow conditioning section to smooth the air flow and reduce turbulence.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 is a photograph of the Curved Duct Test Rig. A brief description of the test rig is presented here, and more details are found in previous papers by the authors [2,3]. Air is supplied to the test rig from a centralized air supply and passes through a set of mufflers (not shown in the photograph), an elbow with turning vanes, and a flow conditioning section to smooth the air flow and reduce turbulence.…”
Section: Introductionmentioning
confidence: 99%
“…This liner was designed to provide the maximum attenuation in the middle of the useable frequency range (~1500 Hz) and at the maximum flow speed (Mach 0.275) of the CDTR at the time. The authors reported on evaluations of this in-house-designed liner (Liner L01) in a previous paper [2].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous paper 13 the authors outlined the procedure by which sound measured at the duct walls is used to determine the complex amplitudes of the modes. The modal amplitudes are used to determine the sound pressure and acoustic velocity of each modal component in a method outlined in a previous paper by the authors 14 . The sound pressure p mn and acoustic velocity u mn are used to evaluate Morfey's 15 expression for the axial acoustic intensity of the (m,n) modal component, I mn , in uniform axial flow:…”
Section: A Attenuation Computation From Measured Datamentioning
confidence: 99%
“…Figure 1 is a photograph of the Curved Duct Test Rig. A brief description of the test rig will be presented here, and more complete description of the rig can be found in previous papers by the authors 13,14 . Air is supplied to the test rig from a centralized air supply and passes through a set of mufflers (not shown in the photograph), an elbow with turning vanes, and a flow conditioning section to smooth the air flow and reduce turbulence.…”
Section: Introductionmentioning
confidence: 99%